An Integrated View on Regional Economic Research - Michał BILCZAK; Kornelia SZMIT (Communications of International Proceedings, 2021)
The article considers the main aspects of an integrated approach to the study of the region. The theoretical aspects of the study of the region as an integral socio-economic system, as well as approaches to the typology and classification of regions are considered. Specific methods of innovation and social development indices are given. The stratification approach is used, which is extremely important for evaluating the resources and potential of specific territories. The system of regional accounts, sustainable development of industries and complexes of regions are studied. The level of development and quality of life of the population using the human development index is presented. Attention is paid to the development of the fishery complex of the Kaliningrad Oblast.
Keywords: stratification; typology; classification of regions; system of regional accounts; human development index.